The impact of early age-related hearing loss on working memory capacity and speech recognition in noise in middle-aged and older adults - Chen-Wei Chang; Yu-chun Chen (Experimental Gerontology, 2025)
Purpose: This study aimed to investigate the impact of age-related hearing loss (ARHL) on working memory capacity (WMC) and speech recognition in noise and their relationship in middle-aged and older adults. Methods: Participants were divided into three groups: young adults with normal hearing, middle-aged and older adults with normal hearing, and middle-aged and older adults with high-frequency hearing loss. Assessments included standard and extended high-frequency (EHF) audiometry, the Wechsler Memory Scale, and the Taiwanese Mandarin Quick Speech-in-Noise test. Results: Sixty-two participants were recruited. Early ARHL were evident as elevated thresholds >1 kHz and in the EHF range. Conventional high-frequency hearing loss primarily impaired word recognition in quiet, whereas EHF loss significantly affected speech-in-noise recognition. Furthermore, ARHL was associated with reduced WMC, potentially accelerating cognitive decline. After controlling for age and hearing status, no significant associations were found between signal-to-noise-ratio (SNR) loss and hearing measures, including EHF hearing thresholds. However, WMC remained moderately and negatively correlated with SNR loss in middle-aged and older adults (r = −0.554, p = .002) but not in younger adults. Conclusion: Adults aged ≥50 years showed declines in EHF hearing sensitivity, WMC, and speech-in-noise recognition despite clinically normal hearing or well-preserved hearing. Speech-in-noise testing proved more sensitive than pure-tone audiometry or word recognition in detecting auditory and cognitive decline. To comprehensively evaluate the impact of ARHL on communication in middle-aged and older adults, it is recommended to incorporate assessments of EHF hearing sensitivity, cognitive function (e.g., WMC), and speech-in-noise perception.